Habitat Characteristics of Anopheles sp. Larvae as Malaria Vectors in Mata Air Village, Kupang Tengah District - Felderika Pandie; Ragu Theodolfi; Oktofianus Sila; Johanes Jusuf Pitreyadi Sadukh; Erika Maria Resi; Karolus Ngambut; Ragu Harming Kristina; Wanti `Wanti (Poltekkes Kemenkes Kupang, 2025)
Malaria is caused by plasmodium transmitted through the bite of an infected female Anopheles. Indonesia, especially NTT Province, is endemic to malaria. Mata Air Village is located in the Tarus Health Center area of ​​Kupang Regency with a high total of cases in 2017, namely 502 patients. The purpose of this study was to identify the characteristics of the location of Anopheles larvae growth in Mata Air Village. This descriptive study describes the characteristics of the location of Anopheles larvae breeding in Mata Air Village. The variables studied include the type of breeding site, water temperature, water pH, water salinity, and density of larvae. The study sample included all locations that have the potential to be breeding sites for Anopheles larvae. The analysis was carried out descriptively to describe the characteristics of the Aedes growth location. The results showed that the most common habitat was swamps with a percentage of 21.43%, while the least common habitats were puddles, dry coconut residue, and livestock drink containers, each at 7.14%. The habitat types found consisted of permanent at 35.71% and temporary at 64.29%. The highest water temperature was recorded in the rice field habitat with a value of 30°C, while the lowest temperature was found in the remains of dry coconuts with a value of 26°C. The highest pH value in the rice fields reached 8, while the lowest pH value was found in used buckets, leftover dry coconuts, and leftover wheels, each of which was 6. The salinity value in all habitats was detected to be empty. The average density of high Anopheles larvae was found in dirty puddles with a value of around 2.7 per scoop, while no larvae were found in irrigation channels. With the discovery of Anopheles habitat in the swamp, it is recommended to consider fish farming in the swamp area or to fill the swamp, or to drain the swamp water to a lower area, so that it is hoped that there will be no more puddles and Anopheles larvae around the settlement.